A New Raster-Based Metric to Measure Relative Food Availability in Rural Areas: A Case Study in Southeastern North Carolina. - MULROONEY, TIMOTHY; MCGINN, CHRIS; BRANCH, BENJAMIN; MADUMERE, CHIBUIKE; IFEDIORA, BYRON (Southeastern Geographer)
The study of food deserts and food swamps explore access to food sources, the overabundance of health ailments directly related to obesity and poor diet, as well as the relationships between the two. There are various ways to quantitatively measure tenets of food deserts and food swamps, such as food availability, using GIS (Geographic Information Systems). Absolute metrics attached to density (healthy food outlets per square mile), linear (miles) or time (minutes) units used to measure food availability are being replaced by relative metrics that comparatively express units against each other. We developed a way to measure relative food availability using a pixel-based relative travel-time index (PRTI). The PRTI measures travel-time to the nearest healthy food source versus that to the nearest unhealthy food source at the pixel level. The result is a high-resolution surface that can analyzed on its own or agglomerated for comparison's sakes. In areas with lower relative availability of healthy foods, preliminary analysis has shown differences between socio-economic variables in rural regions compared to a high availability counterpart. Distinct differences between the PRTI and other metrics used to measure food availability are evident. These results can lead to an increased understanding of food-needy areas not constrained by man-made boundaries at scales necessary to facilitate necessary interventions.